Phosphodiesterase Type 5 Inhibitors for the Treatment of Male Lower Urinary Tract Symptoms - Kaplan, Steven A (MedReviews, LLC, 2007)
Both lower urinary tract symptoms due to benign prostatic hyperplasia (BPH) and erectile dysfunction have a very high prevalence among aging men, and there is some clinical evidence that they may share a common pathophysiology. Consequently, several preliminary studies of phosphodiesterase type 5 inhibitors—sildenafil and tadalafil—have recently been conducted in men with concomitant erectile dysfunction and lower urinary tract symptoms to determine whether these agents are effective for the treatment of symptomatic BPH. These studies have demonstrated efficacy, both alone and in combination with an α-blocker, in treating lower urinary tract symptoms along with sexual dysfunction. However, larger-scale randomized studies are necessary to determine long-term safety, efficacy, and cost effectiveness.